1982
DOI: 10.1016/s0006-3495(82)84520-7
|View full text |Cite
|
Sign up to set email alerts
|

Improved fluorescent probes for the measurement of rapid changes in membrane potential

Abstract: To improve the quality of fluorescent voltage-sensitive probes twenty new styryl dyes were synthesized. Some of the new probes are significantly better than any used in the past. A signal-to-noise ratio of 90 root mean square (rms) noise was obtained for an optical recording of action potentials from neuroblastoma cells maintained in monolayer culture. The fluorescence fractional change of the optical signal is as large as 14%/100 mV. Photodynamic damage and bleaching are much less significant with the new pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
159
1
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(173 citation statements)
references
References 22 publications
8
159
1
1
Order By: Relevance
“…The observed changes of the fluorescent dye may not be generated by transmembrane potentials but by changes of local electrical fields mainly on the basis of the mechanism of electrochromy Grinvald et al, 1982). Therefore this principle should also be applicable for SR membranes.…”
Section: Discussionmentioning
confidence: 99%
“…The observed changes of the fluorescent dye may not be generated by transmembrane potentials but by changes of local electrical fields mainly on the basis of the mechanism of electrochromy Grinvald et al, 1982). Therefore this principle should also be applicable for SR membranes.…”
Section: Discussionmentioning
confidence: 99%
“…It was possible to average 100 trials with no noticeable change in action potential amplitude or waveform (Antic and Zecevic, 1995). Mammalian slice preparations have generally been found to be more sensitive to photodynamic injury than invertebrate preparations (Grinvald et al, 1982;Antic et al, 1999). Mitral cells, however, tolerated well the high-intensity excitation light during successive recording trials if the exposures were kept relatively short (100 -200 msec) and separated by dark intervals lasting several minutes.…”
Section: Methodsmentioning
confidence: 99%
“…However, C-2 reversed phase silica eluted with a gradient from 1% acetic acid in water to methanol yielded 130 mg blue solid (0.051 mmol, 23%). MALDI-TOF m/z 2531 (M+, 14%), 2575 (13), 2487 (13). Polydispersity of the PEG reagent resulted in a series of product peaks ranging from m/z 2004-3104 with 44 m/z increments.…”
Section: -[(E)-2-(5-{(e)-2-[4-(dibutylamino)phenyl]ethenyl}-thiophenmentioning
confidence: 99%
“…Many styryl dyes, including the series of RH and JPW dyes, have been synthesized with a range of excitation and emission wavelengths and a variety of voltage responses. 5,6,13,14 VSDs that have high quantum yields and produce a large change in fractional fluorescence (ΔF/F) are desireable because they generate adequate signals at lower dye concentrations. Recently, Salama et al reported a series of long-wavelength VSDs designed to report cardiac action potentials (APs) from deeper layers of the heart by incorporating a thienyl group in the polymethine bridge to maintain the rigidity of the styryl chromophore while extending the fluorescence wavelengths.…”
Section: Introductionmentioning
confidence: 99%